2005
DOI: 10.1111/j.1600-0781.2005.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A exposure alters adhesive properties of mouse melanoma cells

Abstract: Our results suggest that UVA radiation appears to alter the adhesive properties of melanoma cells in vitro, by diminishing the melanoma-melanoma adhesion and by increasing melanoma adhesion to the endothelium. This suggests that UVA exposure might increase the metastatic capability of the melanoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…injection is a metastasis-like event resembling the hematogenous metastasis of melanoma and gives an indication of their metastatic potential, as shown by Fidler [17,18]. We have also demonstrated that UVA exposure causes the increase in the adhesiveness melanoma cells to endothelium in vitro , what is accompanied by changes in the expression of the cell surface adhesion molecules [19]. Thus, we proposed that the UVA-derived changes in the expression of adhesion molecules could be, at least in part, responsible for the in vivo observed increase of pulmonary tumor colonies in mice.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…injection is a metastasis-like event resembling the hematogenous metastasis of melanoma and gives an indication of their metastatic potential, as shown by Fidler [17,18]. We have also demonstrated that UVA exposure causes the increase in the adhesiveness melanoma cells to endothelium in vitro , what is accompanied by changes in the expression of the cell surface adhesion molecules [19]. Thus, we proposed that the UVA-derived changes in the expression of adhesion molecules could be, at least in part, responsible for the in vivo observed increase of pulmonary tumor colonies in mice.…”
Section: Introductionmentioning
confidence: 74%
“…UVB radiation was filtered out with a 5 mm thick glass filter. The spectral irradiances were measured with a temperature stabilized Bentham DM150 (Bentham Instruments Ltd., Berkshire, England) double-monochromator spectroradiometer at 0.5 nm intervals from 250 nm to 400 nm as described previously [16,19]. …”
Section: Methodsmentioning
confidence: 99%
“…The four hour time-point was selected in order to give melanoma cells time to respond to UVA radiation in transcriptional level. Furthermore, 4-h time-point was also used in our preliminary in vitro set-up, where we have observed alterations in the adhesive properties of the melanoma cells 4 hours after the end of irradiation [14]. …”
Section: Discussionmentioning
confidence: 99%
“…The irradiances of the UVA source were measured as described previously [14,28]. Briefly, the irradiances were determined with a temperature- and wavelength-controlled Optronic 742 double-holographic grating spectroradiometer having a Teflon diffuser as input optics at 1 nm intervals from 250 to 400 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation